Active uncoiling and feeding of a continuum arm robot. (April 2019) - Palmer, D.; Axinte, D.
Highlights: Ability to reach a targeted point by compensating for the helix angle of the coiling drum. Develop smart planned motions to allow Tip Following for the navigation of the continuum robot. Develop time and position effective algorithms for the above so that the uncoiling and feeding of the slender robot can be demonstrated effectively. Abstract: Continuum arms are becoming more popular for use in inspection and repair of hard to reach environments, typically in-situ. These applications characteristically have less space outside the scenario as well as internally. Previous approaches require a significant footprint in this area, potentially limiting the possible exploitations. The algorithm reported within this paper demonstrates a method to actively coil / uncoil a continuum arm on a helical drum, which can be applied to multiple trajectories within a practical computation time. Deviations from desired trajectory are below 3 mm or 1°, individual steps calculated on average in 0.031 s, or complete computation for new trajectory within 170 s.